Preparation and Characterizations of Nanocellulose from Wood Pulp using Hydrolysis Method - Nguyen, Trung Thanh; Nguyen, Hoang Chung; Chu, Thi Hoa; Le, Quang Dien (Old Journal, 2019)
Nanocellulose was prepared from wood pulp by hydrolysis method using H₂SO₄ 60% wt at 45°C for 60 minutes with ratio solid/solution of 1/10. Suspension was cleaned into neutral by centrifuge followed by ultrasonication treatment at room temperature for 2 hours. Nanocellulose was characterized by X-ray diffraction (XRD), Scan electron microscopy (SEM) and Fourier Transform Infrared (FT-IR). Obtained nanocellulose is cellulose nanocrystal (CNC) with dimensions of 20-30 nm x 100-300 nm and crystallinity index of 90%.